Tenax extraction of sediments to estimate desorption and bioavailability of hydrophobic contaminants: A literature review. (6th January 2015) - Lydy, Michael J; Harwood, Amanda D; Nutile, Samuel A; Landrum, Peter F
ABSTRACT: Characterizing sediment‐associated hydrophobic contaminants is problematic, because assessing the total amount of a compound available for chemical exchange with an organism is difficult. To address this, contaminant concentrations have been normalized for specific sediment characteristics (including organic C content) or the chemical activity has been estimated using passive samplers. Another approach to assess compound availability is to determine the extent of readily desorbed compound using resin extractions of sediment slurries. The present paper reviews the literature that uses Tenax® TA, a 2, 6‐diphenylene‐oxide polymer as an extraction tool to measure bioavailability of hydrophobic organic contaminants in sediment. Some work has assessed the extent of desorption with sequential extractions to characterize the maximum rate and pool sizes for different desorbing fractions of bound contaminant. As such, the rapidly desorbing fraction has been well correlated with the extent of degradation, bioaccumulation, and toxicity of hydrophobic contaminants. A shortcut to measuring the full desorption curve to determine the rapidly desorbing compound is to use a single‐point extraction, with 6 h or 24 h extractions being the most common. The Tenax extraction has been shown to be effective with laboratory‐spiked sediments, field‐collected sediments, laboratory‐exposed organisms, field‐collected organisms, and studies among laboratories. Furthermore, a literature‐based model has described the bioaccumulation of polychlorinated biphenyls from independently measured field‐collected sediments. Despite the success of this approach, applying the Tenax method to manage contaminated sediments is limited by the absence of a standard set of conditions to perform the extractions, as well as standard methods for using field sediments. Integr Environ Assess Manag 2015;11:208–220. © 2014 SETAC Key Points: The current paper reviews the literature using Tenax TA, a p‐2, 6‐diphenylphyleneoxide polymer. The Tenax extraction has been shown to be effective with laboratory‐spiked sediments, field‐collected sediments, laboratory‐exposed organisms, field‐collected organisms and studies among laboratories, and a literature‐based model has been developed that described the bioaccumulation of polychlorinated biphenyls from independently measured field‐collected sediments. Despite the success of this approach, application of the Tenax method for management of contaminated sediments is limited by the absence of a standard set of conditions for performing the extractions and standard methods for using field sediments.